2005
DOI: 10.1097/01.sap.0000168160.86221.e9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Alters Gene Expression in an in Vitro Model of Hypertrophic Scarring

Abstract: Fibroblasts represent a highly mechanoresponsive cell type known to play key roles in normal and pathologic processes such as wound healing, joint contracture, and hypertrophic scarring. In this study, we used a novel fibroblast-populated collagen lattice (FPCL) isometric tension model, allowing us to apply graded biaxial loads to dermal fibroblasts in a 3-dimensional matrix. Cell morphology demonstrated dose-dependent transition from round cells lacking stress fibers in nonloaded lattices to a broad, elongate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 21 publications
(29 reference statements)
0
43
0
Order By: Relevance
“…3 More recent work has shown that fibroblast gene expression, including apoptosis signaling, matrix metalloproteinase (MMP) activity, and differentiation into myofibroblasts, are strongly linked to the rigidity or laxity of the ECM, even independent of transforming growth factor (TGF)-b signaling. [42][43][44][45][46][47][48] Even a 15% increase in cell stretch is capable of altering a fibroblast's orientation in relation to the ECM, inducing alterations in focal adhesion kinase signaling, or up-regulating expression of alpha smooth muscle actin (aSMA), consistent with differentiation into the contractile myofibroblast. 49,50 Some clinicians have theorized that reducing the tension on wound fibroblasts by paralyzing local muscle fibers may reduce myofibroblast proliferation and collagen production, thereby decreasing scarring.…”
Section: Collagen-mediated Mechanical Tensionmentioning
confidence: 99%
“…3 More recent work has shown that fibroblast gene expression, including apoptosis signaling, matrix metalloproteinase (MMP) activity, and differentiation into myofibroblasts, are strongly linked to the rigidity or laxity of the ECM, even independent of transforming growth factor (TGF)-b signaling. [42][43][44][45][46][47][48] Even a 15% increase in cell stretch is capable of altering a fibroblast's orientation in relation to the ECM, inducing alterations in focal adhesion kinase signaling, or up-regulating expression of alpha smooth muscle actin (aSMA), consistent with differentiation into the contractile myofibroblast. 49,50 Some clinicians have theorized that reducing the tension on wound fibroblasts by paralyzing local muscle fibers may reduce myofibroblast proliferation and collagen production, thereby decreasing scarring.…”
Section: Collagen-mediated Mechanical Tensionmentioning
confidence: 99%
“…Mechanical stimulation has been found in vitro to activate calcium mediated intracellular signaling in fibroblasts [17]. Human dermal fibroblasts have a linear increase in type I and III collagen and collagenase gene expression with increasing mechanical loads [18]. Human keloid fibroblasts increase transcription of TGFbeta 1 and 2 following mechanical strain when compared to normal fibroblasts [19].…”
Section: Tensionmentioning
confidence: 98%
“…The cornea is a dynamic tissue, capable of altering its ECM composition and biomechanical properties in response to changes in the visual environment (31,32). In addition, corneal fibroblasts have been demonstrated to respond actively to local tension changes in the ECM (33), and fibroblasts are a major type of mechanoresponsive cell (34). However, to date, there have been no reports regarding the effect of mechanical stretch on expression of MMP and TIMP in HKCFBs.…”
Section: Introductionmentioning
confidence: 96%